Analyse De L’évolution Saisonnière Des Matières Oxydables Dans Le Secteur Oriental De La Lagune Ebrié (Côte d’Ivoire) - Jean-Gaël, Irié B.T.; Valérie, Wognin A.; Marie-Laure, Kando A.; Natcha, Aka; Maurice, Aka A.; Sougo, Coulibaly A.; Sylvain, Monde (European Scientific Journal, ESJ, 2018)
Faced with the extension of the cities of Grand-Bassam and Abidjan along the Ebrié lagoon and the lack of data on the oxidizable content in the eastern sector of the Ebrié lagoon, this study was initiated. It aims to determine the levels of oxidizable materials in the eastern sector of the Ebrié lagoon. PH, temperature, salinity and dissolved oxygen were determined in situ at thirtyone (31) stations during the dry season and the rainy season. On these same stations, water samples were also taken per season to determine the content of oxidizable matter according to the methods in force. The statistical treatment consisted in knowing the links between the hydrological parameters. The average values of the parameters in the rainy season and in the dry season are 5,98 and 7,28 respectively for the pH, 27,59 °C and 29,6 °C for the temperature, 5,01 and 19,48 for salinity, 6.14 mg/L and 3.78 mg/L for dissolved oxygen, 0.24 mg/L and 0.38 mg/L for ammonium, 0.089 mg/L and 0.036 mg/L for nitrite, 8.18 mg/L and 0.23 mg/L for nitrate, 1.57 mg/L and 1.78 mg/L for orthophosphate, 76.06 mg/L and 56.81 mg/L for COD and 40.23 mg/L and 34.16 mg/L for BOD5. The evolution of oxidizable matter depends on the entry of continental, oceanic and precipitation waters into the lagoon. The high levels of oxidizable materials are observed in large part in the berries. Good positive correlations are observed between COD and DBO5 and between salinity and nitrite. Temperature and salinity have a good negative correlation. Lagoon waters receive more oxidizable materials in highly urbanized areas than in areas with little or no urbanization.